Analisis Penggunaan Bahasa terhadap Keefektifan Komunikasi Matematis dalam Kegiatan Interaktif Pembelajaran Matematika Kelas 12 SMAN 1 Baleendah - Aan Hasanah, Najla Fauziyyah Yusuf, Tatang Herman dan (STKIP Paris Barantai, 2025)
The aims of the research to analyze the effect of language use on the effectiveness of mathematical communication in interactive mathematics learning. The language used by teachers has an important role in conveying mathematical concepts clearly and easily understood by students. This study used mixed-method, which combines quantitative and qualitative approaches, involving 39 12th grade students at SMAN 1 Baleendah. Data were collected through questionnaires consisting of closed and open-ended questions. The analysis showed that the use of appropriate and understandable language by teachers can improve the effectiveness of mathematical communication and students' understanding of mathematical materials. In addition, group discussion is an important tool in deepening concept understanding. However, there were challenges in understanding more complex mathematical terms, indicating the need for more contextualized language and more adaptive teaching approaches. This study recommends that teachers pay attention to the use of clear language and create more interactive and inclusive learning.